Pertanggung Jawaban Pidana Dokter Dalam Menjalankan Profesinya Menurut KUHP - Meli Hertati Gultom (Visi Sosial Humaniora, 2022)
The profession of doctor ia one of the Noble profession, because the task of saving the soul of people who is suffering from a disease, that man performs the task or profession is not always perfect, there can be mistakes and the souls can happen intentionally and or accidentally. Every other profession can generally be asked for criminal accountability when fulfilling elements of error, including the profession of doctors. The purpose of this writing to know the responsibility of the Professional Professional Doctor and Law on the profession of the doctor. This research method is a journightative normative method. The research shows the profession of physicians may be asked for criminal accountability when proven to meet the element of element of error. The error is the most important element in determining the criminal accountability. The property of the physician profession in Indonesian criminal law indirectly can be subject to sanctions as per article contained in the Criminal Code, and the profession of physicians may be held accountability through the Law and Medical Law and if they do malpractice can be reported and examined the Indonesian Medical Discipline Human Discipline. In conclusion, the profession of physicians may be asked for criminal accountability when it fulfills the elements of an error.